Efek Lama Penyimpanan Semen Beku Sapi Bali pada Pos Inseminasi Buatan terhadap Membran Plasma, Tudung Akrosom Utuh, dan DNA Spermatozoa - Fikri Ardhani; Hayatul Mufidah; Rahmah Samsuriati; Hilman Pratama Putra (Politeknik Negeri Jember, 2020)
The purpose of this study was to determine the effect of frozen storage time for Bali Bull in artificial insemination station in Samarinda City, East Kalimantan on the quality of motility, viability, velocity, abnormality, plasma membrane integrity (MIn), acrosome integrity (AIn), and DNA damage of spermatozoa. The study design used a completely randomized design (CRD) with 5 treatments (storage time) and 5 replications. Frozen semen of Bali Bull used in 2009 (10 years of storage), 2011 (7 years of storage), 2013 (5 years of storage), 2015 (3 years of storage), and 2017 (1 year of storage). The storage time of frozen semen stored for one to ten years in liquid nitrogen at the artificial insemination station in Kota Samarinda, East Kalimantan was still suitable for use in artificial insemination based on motility quality (44.99±2.40%), viability (55.33±2,60%), velocity (0.050±0.002 mm/sec), abnormality (12.87±1.09%), plasma membrane integrity (58.83 ± 1.86%), acrosome integrity (75.48 ± 1 , 61%), and DNA damage of spermatozoa (1.60 ± 0.21%).